Corrosion-resistant grain boundary diffusion neodymium-iron-boron magnet and preparation method thereof

By using ZnαLiβMn100-α-β alloy as the diffusion source, grain boundary diffusion modification is carried out, and the problem of corrosion of neodymium iron boron magnets in harsh environments is solved, achieving efficient corrosion resistance improvement and magnetic performance optimization.

CN119694773AInactive Publication Date: 2025-03-25ANHUI UNIV

Patent Information

Application Number
CN202510206295.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing neodymium iron boron magnets are easily corroded in high temperature, high salt, warm and humid, and electrochemical environments, resulting in a shortened service life. Traditional corrosion-resistant measures have problems such as decreasing magnetic properties and increasing production costs.

Method used

ZnαLiβMn100-α-β alloy is used as the diffusion source, and the diffusion modification of the grain boundaries of the neodymium iron boron magnet is achieved through mechanical processing, diffusion agent coating and two-stage heat treatment processes, forming a Li-rich protective layer to improve the corrosion resistance of the magnet.

Benefits of technology

It significantly improves the corrosion resistance of magnets, extends service life, and maintains the improvement of magnetic properties, breaking the trade-off between traditional corrosion resistance and magnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119694773A_ABST
    Figure CN119694773A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of rare earth permanent magnet materials, in particular to a corrosion-resistant grain boundary diffusion neodymium-iron-boron magnet and a preparation method thereof.The preparation method comprises the steps that a sintered neodymium-iron-boron blank is obtained, a diffusion source is obtained, a grain boundary diffusant is modulated, the diffusion source is Zn alpha Li beta Mn 100-alpha-beta alloy according to the mass ratio (wt.%), alpha is larger than or equal to 60 wt.% and larger than or equal to 10 wt.%, the neodymium-iron-boron blank is treated, and the grain boundary diffusant is prepared; and coating the surface of the magnet with a diffusant to obtain a composite magnetic sheet, and carrying out grain boundary diffusion heat treatment on the composite magnetic sheet to obtain the corrosion-resistant grain boundary diffusion neodymium-iron-boron magnet. The diffusion source used in the method is low in price and high in matching degree with traditional equipment, raw materials are not required to be additionally purchased except the diffusion source, the cost performance is high, the corrosion-resistant weight loss ratio can be effectively reduced, the residual magnetism and coercive force of the magnetic performance of the magnet are slightly improved compared with those of a blank magnet, the problem of balancing the corrosion resistance and the magnetic performance is solved, and the service life of the magnet is prolonged. And the obtained corrosion-resistant grain boundary diffusion neodymium-iron-boron magnet is excellent in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rare earth permanent magnetic materials, and in particular to a corrosion-resistant grain boundary diffusion NdFeB magnet and a preparation method thereof. Background Art

[0002] NdFeB rare earth permanent magnet materials have excellent performance and are widely used in many fields such as new energy vehicles, wind power generation, medical equipment, robots and consumer electronics. These service scenarios include high temperature, high salt, warm and humid, electrochemical environment, etc., which are very demanding on the corrosion resistance of magnets. Since sintered NdFeB contains 3-7 wt.% of rare earth-rich grain boundary phase, it is easy to be corroded and denatured, resulting in grain shedding, which affects the service life of the magnet. Usually, the corrosion resistance of NdFeB magnets is improved by electroplating Ni, Zn on their surface or directly coating them with organic coatings such as epoxy resin to inhibit corrosion by preventing direct contact between the substrate and the environment. However, the coating inevitably has a variety of sharp contacts during transportation, assembly, and use, causing surface damage such as perforation and microcracks. The magnet will be quickly corroded from the damaged coating, seriously affecting the service performance. Therefore, the corrosion resistance of the magnet itself needs to be further improved.

[0003] In addition, improving the corrosion resistance of sintered NdFeB from the perspective of the magnet's own composition design is called alloying treatment. By adding some alloying elements, such as Al, Cu, Ge, Sn, V, Mo, W, Nb, Ti, Zr, etc., a new intergranular phase can be formed, the chemical activity can be reduced, the corrosion potential can be increased, and the corrosion rate can be reduced. However, it should be noted that excessive addition of alloying elements will reduce the magnetic properties and the temperature stability of the magnet, increase the difficulty of mechanical processing, and increase the production cost. From a mechanistic point of view, most of the corrosion starts from the rare earth-rich grain boundary phase on the surface of the NdFeB magnet. If the grain boundary can be modified and the active surface rare earth-rich grain boundary is transformed into a more difficult to corrode substance, the service life of the magnet can be extended. Grain boundary diffusion technology usually uses heavy rare earth to improve the coercive force of the magnet, and the principle includes the modification of the grain boundary. However, this technology requires the diffusion source to cooperate with the process, so there is still little research on corrosion resistance. The problems mainly focus on the development of new corrosion-resistant and cheap diffusion sources and the supporting diffusion process to realize the grain boundary diffusion process without negatively affecting the magnet performance. Summary of the invention

[0004] The object of the present invention is to provide a corrosion-resistant grain boundary diffused NdFeB magnet and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides a technical solution: a method for preparing a corrosion-resistant grain boundary diffused NdFeB magnet, wherein the base magnet has a mass ratio (wt.%) of RE xFe (100-x-a-b) B a M b , 33wt%≥x≥29.5wt%, 1.05wt%≥a≥0.92wt%, wherein RE is one or more of Pr, Nd, Dy, Tb, Ho, Ce, and Y in the lanthanide rare earth elements, B is at least one of Dy and Tb, and M is one or more of Co, Zr, Ti, Nb, Cu, Ga, Al, and Zn, and the preparation method comprises the following steps: Step S1, obtaining a sintered NdFeB blank as a base magnet; Step S2, obtaining a diffusion source and preparing a grain boundary diffusion agent, wherein the diffusion source is Zn in terms of mass ratio (wt.%). α Li β Mn 100-α-β Alloy, 60wt.%≥α≥10wt.%; Step S3, machining the sintered NdFeB blank; Step S4, coating the diffusant on the surface of the magnet to obtain a composite magnetic sheet; Step S5, subjecting the composite magnetic sheet to grain boundary diffusion heat treatment, the primary heat treatment temperature is 850-1000°C, the time is 2-8h, after reaching the primary heat treatment temperature, 0.5-1.5h, 50-80kPa high purity argon is given, and then discharged through the vacuum system, and the vacuum degree is maintained for the rest of the primary heat treatment time. -5 The secondary heat treatment temperature is 450-600℃, the time is 2-6h, and the vacuum degree is maintained at 10 -5 After the two-stage heat treatment, argon gas is introduced to make the gas pressure in the furnace reach 80-100kPa, and rapid cooling is performed to obtain corrosion-resistant grain boundary diffusion NdFeB magnets.

[0006] The order of the above steps can be changed without causing any logical conflicts.

[0007] Preferably, in step S2, the diffusing agent comprises a diffusion source (60-80 wt.%), a binder (2-5 wt.%), and a solvent (15-38 wt.%).

[0008] Preferably, the binder is polyvinyl butyral or polyvinyl alcohol.

[0009] Preferably, the solvent is anhydrous ethanol or ether.

[0010] Preferably, the diffusion source Zn α Li β Mn 100-α-βIn the alloy, 60wt.%≥α≥10wt.%, 80wt.%≥β≥0wt.%, and the mass ratio of the diffusion source: the binder: the solvent is 68±2: 4±0.5: 28±2.5.

[0011] Preferably, in step S3, the blank is machined by wire-cutting electric discharge machining, and the axial and radial dimensions are controlled to be no more than 20 mm.

[0012] Preferably, in step S3, after the blank is machined, it is sandblasted to clean the surface to remove oil and oxides, and is soaked in a nitric acid solution with a volume ratio of 2.5-5% for 20-30 seconds. After pickling, it is ultrasonically vibrated in alcohol for 2-5 minutes and dried for later use.

[0013] Preferably, in step S4, the diffusant is coated by immersing the magnetic sheet, spraying or printing, and step S4 is performed within 1 hour after step S3. The thickness of the diffusant is 0.5-0.6 mm, and the surface of the diffusant is dried in an oven at a temperature of 60-80°C for 30-60 min.

[0014] The invention also discloses a corrosion-resistant grain boundary diffusion NdFeB magnet, which is obtained by any of the above-mentioned preparation methods.

[0015] The present invention has the advantages that: the Zn used α Li β Mn 100-α-β Alloy diffusion source (60wt.% ≥ α ≥ 10wt.%) is inexpensive, the diffusion process is highly compatible with the equipment used in the traditional sintered NdFeB production line, the entry threshold is low, and no additional purchase of raw materials other than the diffusion source is required. It has high cost performance, effective corrosion resistance and weight loss rate, and improves the anti-corrosion effect. The magnetic properties of the corrosion-resistant grain boundary diffusion NdFeB magnet are slightly improved compared to the remanence and coercive force of the blank magnet, breaking the trade-off between corrosion resistance and magnetic properties in the traditional alloy smelting process. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a line graph of the weight loss rate of comparative example 1 and embodiment 1 changing with time. DETAILED DESCRIPTION

[0017] First of all, it should be noted that the embodiments and the salient features in the embodiments of the present application can be combined with each other without causing any conflict. The present invention will be described in detail below in conjunction with the embodiments.

[0018] Secondly, it should be noted that the raw materials used in the method of the present invention can be easily obtained from the market.

[0019] As mentioned in the background of the present invention, there is a trade-off between magnetic properties and corrosion resistance in the prior art. In order to solve this problem at a lower cost, a typical embodiment of the present invention provides a method for preparing grain boundary diffusion corrosion-resistant NdFeB. The base magnet is composed of RE in weight ratio (wt.%). x Fe (100-x-a-b) B a M b , 33wt%≥x≥29.5wt%, 1.05wt%≥a≥0.92wt%. RE is one or more of Pr, Nd, Dy, Tb, Ho, Ce, Y in the lanthanide rare earth elements, B is at least one of Dy and Tb. M is one or more of Co, Zr, Ti, Nb, Cu, Ga, Al, Zn. The finished base magnet includes Nd2Fe 14 B main phase, rare earth-rich grain boundary phase and a small amount of B-rich phase.

[0020] A method for preparing a corrosion-resistant grain boundary diffusion NdFeB magnet comprises the following steps: Step S1, obtaining a sintered NdFeB blank; Step S2, obtaining a diffusion source and preparing a grain boundary diffusion agent. The diffusion source is Zn α Li β Mn 100-α-β alloy, 60wt.%≥αwt.%≥10; step S3, processing the NdFeB blank; step S4, coating the diffusing agent on the surface of the magnet to obtain a composite magnetic sheet; step S5, performing grain boundary diffusion heat treatment on the composite magnetic sheet to obtain a corrosion-resistant grain boundary diffusion NdFeB magnet with unreduced magnetic properties.

[0021] It should be noted that the preparation of the diffusing agent follows the principle of being able to adhere to the surface of the magnet without falling off.

[0022] The following embodiments of the present invention only select some preferred embodiments for illustration and do not serve to limit the scope of the present invention.

[0023] The beneficial effects that can be achieved by the present invention will be further illustrated below in combination with embodiments and comparative examples.

[0024] Comparative Example 1 is a commercial NdFeB-based magnet used within the scope of the present invention, which only serves as a limitation in the present invention and should not conflict with any other invention. Examples 1-5 are descriptions of the magnetic properties that can be achieved by the preferred diffusion sources and the preferred process combinations within the scope of the present invention. Unless otherwise specified, the remaining steps are carried out according to the above description.

[0025] Commercial base magnet composition: (PrNd) 31.8 Cu 0.15 Al 0.65 Ga 0.12 Co 0.75Zr 0.12 Ti 0.075 Fe 69.385 B 0.95。

[0026] Example 1 Step A1: Morphology processing of commercial base magnets: Use electric spark wire cutting equipment to radially cut commercial sintered NdFeB into magnetic sheets with a diameter of 10 mm and a thickness of 5 mm.

[0027] Step A2: Preparation of diffusant: The diffusion source uses Zn 10 Li 80 Mn 10 The binder is PVB powder, and the solvent is anhydrous ethanol. The diffusion source, the binder, and the solvent are mixed in a mass ratio of 66:4:30 and stirred evenly.

[0028] Step A3: Surface treatment of magnetic sheets: After cutting, the magnetic sheets are sandblasted and polished to reveal the metallic luster. Then, they are immersed in a 3% dilute HNO3 solution for 25 seconds to remove the residual oil and impurities on the surface. Ultrasonic vibration is performed in alcohol for 3 minutes.

[0029] Step A4: After completing step A3, perform coating work: evenly coat the diffusing agent on the surface of the magnet, with a thickness of 0.5 mm.

[0030] Step A5: Drying: Pre-drying is carried out in an oven at a temperature of 70°C for 40 minutes.

[0031] Step A6: Two-stage pressure-changing heat treatment. The first stage heat treatment temperature is 900°C for 4 hours. After reaching the first stage heat treatment temperature, high-purity argon gas at 80 kPa is supplied for 1 hour and then discharged through the vacuum system. The remaining time of the first stage heat treatment is maintained for 10 -5 The secondary heat treatment temperature is 450℃ and the time is 6h. The vacuum degree of the secondary heat treatment is maintained at 10 -5 Pa, argon gas was introduced after the two-stage heat treatment to make the pressure in the furnace reach 80kPa for rapid cooling.

[0032] Embodiment 2: Step A1: Same as in Example 1, the commercial sintered NdFeB magnets are radially cut into magnetic sheets with a diameter of 10 mm and a thickness of 5 mm using an electric spark wire cutting device.

[0033] Step A2: Diffusant preparation: Diffusion source using Zn 10 Li 80 Mn 10The adhesive is PVB powder, and the solvent is anhydrous ethanol. The diffusion source, the adhesive, and the solvent are mixed in a mass ratio of 66:4:30 and stirred evenly. This step is consistent with Example 1.

[0034] Step A3: Surface treatment of magnetic sheets: The cut magnetic sheets are sandblasted and polished to reveal the metallic luster, then immersed in a 3% dilute HNO3 solution for 25 seconds to remove residual oil and impurities on the surface, and then ultrasonically vibrated in alcohol for 3 minutes. The operation process is the same as that of Example 1.

[0035] Step A4: After completing step A3, perform coating work: evenly coat the diffusing agent on the surface of the magnet, with a thickness of 0.6 mm.

[0036] Step A5: Drying: Pre-drying is carried out in an oven at a temperature of 70°C for 40 minutes.

[0037] Step A6: Two-stage pressure-changing heat treatment. The first stage heat treatment temperature is 1000°C for 2 hours. After reaching the first stage heat treatment temperature, high-purity argon gas at 50 kPa is added for 1.5 hours and then discharged through the vacuum system. The remaining time of the first stage heat treatment is maintained for 10 -5 The secondary heat treatment temperature is 600℃, the time is 2h, and the vacuum degree is maintained at 10 -5 Pa, argon gas was introduced into the furnace after the two-stage heat treatment to make the pressure in the furnace reach 100kPa for rapid cooling.

[0038] Embodiment 3: Step A1: Use electric spark wire cutting equipment to radially cut commercial sintered NdFeB into magnetic sheets with a diameter of 10 mm and a thickness of 5 mm.

[0039] Step A2: Diffusant preparation: Diffusion source using Zn 40 Li 20 Mn 40 The binder uses PVB powder and the solvent uses anhydrous ethanol. The diffusion source, binder and solvent are mixed in a mass ratio of 66:4:30 and stirred evenly. Here, only the diffusion source component is different from that in Example 1.

[0040] Step A3: Surface treatment of magnetic sheets: The cut magnetic sheets are sandblasted and polished to reveal the metallic luster, then immersed in a 3% dilute HNO3 solution for 25 seconds to remove residual oil and impurities on the surface, and ultrasonically vibrated in alcohol for 3 minutes. This step is no different from Example 1.

[0041] Step A4: After completing step A3, perform coating work: evenly coat the diffusing agent on the surface of the magnet, with a thickness of 0.6 mm.

[0042] Step A5: Drying: Pre-drying is carried out in an oven at a temperature of 70°C for 40 minutes.

[0043] Step A6: Two-stage pressure-changing heat treatment. The first stage heat treatment temperature is 900°C for 4 hours. After reaching the first stage heat treatment temperature, high-purity argon gas at 80 kPa is added for 0.5 hours and then discharged through the vacuum system. The remaining time of the first stage heat treatment is maintained for 10 -5 The secondary heat treatment temperature is 450℃ and the time is 6h. The vacuum degree of the secondary heat treatment is maintained at 10 -5 Pa, argon gas was introduced after the two-stage heat treatment to make the pressure in the furnace reach 80kPa for rapid cooling.

[0044] Embodiment 4: Step A1: The commercial sintered NdFeB magnets are radially cut into magnetic sheets with a diameter of 10 mm and a thickness of 5 mm by using an electric spark wire cutting device.

[0045] Step A2: Diffusant preparation: Diffusion source using Zn 10 Li 80 Mn 10 The binder is PVB powder, and the solvent is anhydrous ethanol. The diffusion source, binder, and solvent are mixed in a mass ratio of 66:4:30 and stirred evenly, which is consistent with Example 1.

[0046] Step A3: Surface treatment of magnetic sheets: The cut magnetic sheets are sandblasted and polished to reveal the metallic luster, then immersed in a 3% dilute HNO3 solution for 25 seconds to remove residual oil and impurities on the surface, and ultrasonically vibrated in alcohol for 3 minutes. This step is no different from Example 1.

[0047] Step A4: After completing step A3, perform coating work: evenly coat the diffusing agent on the surface of the magnet, with a thickness of 0.5 mm.

[0048] Step A5: Drying: Pre-drying is carried out in an oven at a temperature of 70°C for 40 minutes.

[0049] Step A6: The primary heat treatment temperature is 900°C for 8 hours. No argon is introduced during the primary heat treatment stage, and the vacuum degree is less than 10 -4 Pa, the secondary heat treatment temperature is 450℃, the time is 6h, and the vacuum degree is maintained at 10 -4After the two-stage heat treatment, argon gas was introduced to make the gas pressure in the furnace reach 100 kPa for rapid cooling.

[0050] Embodiment 5: Step A1: Use electric spark wire cutting equipment to radially cut commercial sintered NdFeB into magnetic sheets with a diameter of 10 mm and a thickness of 5 mm.

[0051] Step A2: Diffusant preparation: Diffusion source using Zn 10 Li 80 Mn 10 The binder is PVB powder, and the solvent is anhydrous ethanol. The diffusion source, binder, and solvent are mixed in a mass ratio of 60:3.5:36.5 and stirred evenly. The proportion of the diffusing agent here is different from that in Example 1.

[0052] Step A3: Surface treatment of magnetic sheets: The cut magnetic sheets are sandblasted and polished to reveal the metallic luster, then immersed in a 3% dilute HNO3 solution for 25 seconds to remove residual oil and impurities on the surface, and ultrasonically vibrated in alcohol for 3 minutes. This step is the same as in Example 1.

[0053] Step A4: After completing step A3, perform coating work: evenly coat the diffusing agent on the surface of the magnet, with a thickness of 0.6 mm.

[0054] Step A5: Drying: Pre-drying is carried out in an oven at a temperature of 70° C. for 40 min.

[0055] Step A6: Two-stage pressure-changing heat treatment. The first stage heat treatment temperature is 900°C for 4 hours. After reaching the first stage heat treatment temperature, high-purity argon gas at 80 kPa is added for 1.5 hours and then discharged through the vacuum system. The remaining time of the first stage heat treatment is maintained for 10 -5 The secondary heat treatment temperature is 450℃ and the time is 6h. The vacuum degree of the secondary heat treatment is maintained at 10 -5 Pa, argon gas was introduced after the two-stage heat treatment to make the pressure in the furnace reach 80kPa for rapid cooling.

[0056] Comparative Example 1: Step A1: Morphology processing of commercial base magnets: Use electric spark wire cutting equipment to radially cut commercial sintered NdFeB into magnetic sheets with a diameter of 10 mm and a thickness of 5 mm.

[0057] Step A2: Surface treatment of magnetic sheets: After cutting, the magnetic sheets are sandblasted and polished to reveal the metallic luster. Then, they are immersed in a 3% dilute HNO3 solution for 25 seconds to remove the residual oil and impurities on the surface. Ultrasonic vibration is performed in alcohol for 3 minutes.

[0058] Step A3: After completing step A3, perform coating work: evenly coat the diffusing agent on the surface of the magnet, with a thickness of 0.5 mm.

[0059] Step A4: Drying: Pre-drying is carried out in an oven at a temperature of 70°C for 40 minutes.

[0060] Step A5: Two-stage pressure-changing heat treatment. The first stage heat treatment temperature is 900°C for 4 hours. After reaching the first stage heat treatment temperature, high-purity argon gas at 80 kPa is supplied for 1 hour and then discharged through the vacuum system. The remaining time of the first stage heat treatment is maintained for 10 -5 The secondary heat treatment temperature is 450℃ and the time is 6h. The vacuum degree of the secondary heat treatment is maintained at 10 -5 Pa, argon gas was introduced after the two-stage heat treatment to make the pressure in the furnace reach 80kPa for rapid cooling.

[0061] Comparative Example 2: Step A1: Morphology processing of commercial base magnets: Use electric spark wire cutting equipment to radially cut commercial sintered NdFeB into magnetic sheets with a diameter of 10 mm and a thickness of 5 mm.

[0062] Step A2: Preparation of diffusant: The diffusion source uses Zn 10 Li 80 Mn 10 The binder is PVB powder, and the solvent is anhydrous ethanol. The diffusion source, the binder, and the solvent are mixed in a mass ratio of 66:4:30 and stirred evenly.

[0063] Step A3: Surface treatment of magnetic sheets: After cutting, the magnetic sheets are sandblasted and polished to reveal the metallic luster. Then, they are immersed in a 3% dilute HNO3 solution for 25 seconds to remove the residual oil and impurities on the surface. Ultrasonic vibration is performed in alcohol for 3 minutes.

[0064] Step A4: After completing step A3, perform coating work: evenly coat the diffusing agent on the surface of the magnet, with a thickness of 0.5 mm.

[0065] Step A5: Drying: Pre-drying is carried out in an oven at a temperature of 70°C for 40 minutes.

[0066] Step A6: Two-stage pressure-changing heat treatment. The first stage heat treatment temperature is 800°C for 4 hours. After reaching the first stage heat treatment temperature, high-purity argon gas at 80 kPa is supplied for 1 hour and then discharged through the vacuum system. The remaining time of the first stage heat treatment is maintained for 10 -5 The secondary heat treatment temperature is 450℃ and the time is 6h. The vacuum degree of the secondary heat treatment is maintained at 10 -5Pa, argon gas was introduced after the two-stage heat treatment to make the pressure in the furnace reach 80kPa for rapid cooling.

[0067] Comparative Example 3: Step A1: Morphology processing of commercial base magnets: Use electric spark wire cutting equipment to radially cut commercial sintered NdFeB into magnetic sheets with a diameter of 10 mm and a thickness of 5 mm.

[0068] Step A2: Preparation of diffusant: The diffusion source uses Zn 10 Li 80 Mn 10 The binder is PVB powder, and the solvent is anhydrous ethanol. The diffusion source, the binder, and the solvent are mixed in a mass ratio of 66:4:30 and stirred evenly.

[0069] Step A3: Surface treatment of magnetic sheets: After cutting, the magnetic sheets are sandblasted and polished to reveal the metallic luster. Then, they are immersed in a 3% dilute HNO3 solution for 25 seconds to remove the residual oil and impurities on the surface. Ultrasonic vibration is performed in alcohol for 3 minutes.

[0070] Step A4: After completing step A3, perform coating work: evenly coat the diffusing agent on the surface of the magnet, with a thickness of 0.5 mm.

[0071] Step A5: Drying: Pre-drying is carried out in an oven at a temperature of 70°C for 40 minutes.

[0072] Step A6: First-stage pressure change heat treatment. The first-stage heat treatment temperature is 900°C for 4 hours. During the first hour of the heat preservation stage, maintain 80 kPa of high-purity argon in the sintering chamber. The remaining time is maintained for 10 -5 High vacuum environment below Pa.

[0073] Comparative Example 4: Step A1: Morphology processing of commercial base magnets: Use electric spark wire cutting equipment to radially cut commercial sintered NdFeB into magnetic sheets with a diameter of 10 mm and a thickness of 5 mm.

[0074] Step A2: Preparation of diffusant: The diffusion source uses Zn 10 Li 80 Mn 10 No binder is used, and anhydrous ethanol is used as the solvent. The diffusion source and the solvent are mixed in a mass ratio of 66:30 and stirred evenly.

[0075] Step A3: Surface treatment of magnetic sheets: After cutting, the magnetic sheets are sandblasted and polished to reveal the metallic luster. Then, they are immersed in a 3% dilute HNO3 solution for 25 seconds to remove the residual oil and impurities on the surface. Ultrasonic vibration is performed in alcohol for 3 minutes.

[0076] Step A4: After completing step A3, perform coating work: evenly coat the diffusing agent on the surface of the magnet, with a thickness of 0.5 mm.

[0077] Step A5: Drying: Pre-drying is carried out in an oven at a temperature of 70°C for 40 minutes.

[0078] Step A6: Two-stage pressure-changing heat treatment. The first stage heat treatment temperature is 900°C for 4 hours. After reaching the first stage heat treatment temperature, high-purity argon gas at 80 kPa is supplied for 1 hour and then discharged through the vacuum system. The remaining time of the first stage heat treatment is maintained for 10 -5 The secondary heat treatment temperature is 450℃ and the time is 6h. The vacuum degree of the secondary heat treatment is maintained at 10 -5 Pa, argon gas was introduced after the two-stage heat treatment to make the pressure in the furnace reach 80kPa for rapid cooling.

[0079] Comparative Example 5: Step A1: Morphology processing of commercial base magnets: Use electric spark wire cutting equipment to radially cut commercial sintered NdFeB into magnetic sheets with a diameter of 10 mm and a thickness of 5 mm.

[0080] Step A2: Preparation of diffusant: The diffusion source uses Zn 70 Li 10 Mn 20 The binder is PVB powder, and the solvent is anhydrous ethanol. The diffusion source, the binder, and the solvent are mixed in a mass ratio of 66:4:30 and stirred evenly.

[0081] Step A3: Surface treatment of magnetic sheets: After cutting, the magnetic sheets are sandblasted and polished to reveal the metallic luster. Then, they are immersed in a 3% dilute HNO3 solution for 25 seconds to remove the residual oil and impurities on the surface. Ultrasonic vibration is performed in alcohol for 3 minutes.

[0082] Step A4: After completing step A3, perform coating work: evenly coat the diffusing agent on the surface of the magnet, with a thickness of 0.5 mm.

[0083] Step A5: Drying: Pre-drying is carried out in an oven at a temperature of 70°C for 40 minutes.

[0084] Step A6: Two-stage pressure-changing heat treatment. The first stage heat treatment temperature is 900°C for 4 hours. After reaching the first stage heat treatment temperature, high-purity argon gas at 80 kPa is supplied for 1 hour and then discharged through the vacuum system. The remaining time of the first stage heat treatment is maintained for 10 -5 The secondary heat treatment temperature is 450℃ and the time is 6h. The vacuum degree of the secondary heat treatment is maintained at 10 -5Pa, argon gas was introduced after the two-stage heat treatment to make the pressure in the furnace reach 80kPa for rapid cooling.

[0085] The magnetic properties of the corrosion-resistant grain boundary diffusion NdFeB magnet of the present invention and the comparative examples outside the protection scope of the present invention are shown in Table 1 below: Table 1 ;

[0086] The weight loss rate in the aging box is used as the evaluation standard. The conditions in the aging box are 120℃, 2bar and 100% relative humidity. After the magnet is ground and polished with metallographic sandpaper, it is ultrasonically cleaned in an ultrasonic cleaner. After drying, the mass before corrosion M1 is weighed. After being exposed to the aging box for 24 h, 48 h, 72 h and 96 h, the surface corrosion products are cleaned, ultrasonically cleaned and dried, and the mass of the corrosion stage M2 is weighed. S is the surface area of ​​the sample. The calculation formula is weight loss rate = (M1-M2) / S*100%.

[0087] The corrosion resistance weight loss rate study results of the above-mentioned embodiment and comparative example magnets are shown in Table 2 below.

[0088] Table 2 ;

[0089] In order to more intuitively demonstrate the beneficial effects of the present invention, the weight loss rate variation over time of Comparative Example 1 and Example 1 is preferably obtained, as shown in FIG. Figure 1 As shown, it can be clearly seen that compared with Comparative Example 1, the corrosion resistance weight loss rate of Example 1 at 24h, 48h, 72h and 96h is significantly lower.

[0090] The mechanism of action of the present invention is that after the diffusion heat treatment, a diffusion layer is formed within 200 microns from the surface of the finished magnet to the inside of the magnet. The diffusion layer is rich in Li, and Li, as an excellent anti-corrosion material, has a much higher corrosion resistance than the blank NdFeB magnet. In addition, after the grain boundary diffusion, Nd2Fe 14 The B main phase grains grow from an average of 3-5 microns to more than 10 microns, forming a tighter organizational structure, reducing the specific surface area and the contact area, effectively playing an anti-corrosion role and reducing the corrosion resistance weight loss rate.

[0091] Comparison of experimental results Magnetic properties comparison: From the data in Table 1, it can be seen that compared with Comparative Example 1 (without grain boundary diffusion process), the remanence Br of Example 1 is increased from 13.20kGs to 13.50kGs, the coercivity Hcj is changed from 16.68kOe to 16.73kOe, the maximum magnetic energy product BHmax is increased from 42.19MGOe to 43.54MGOe, and the squareness Q is slightly changed. This shows that the grain boundary diffusion process has a significant optimization effect on the magnetic properties of the magnet and improves the comprehensive magnetic performance indicators of the magnet.

[0092] By comparing Examples 2-5 with Example 1, changing different process parameters such as primary heat treatment temperature, diffusion source composition, atmosphere control during heat treatment, diffusion agent formulation, etc., will cause different changes in various indicators of magnetic properties, indicating that these process parameters have a key influence on the magnetic properties and need to be finely controlled.

[0093] Corrosion resistance comparison: The weight loss rate in the aging box is used as the corrosion resistance evaluation standard, and the aging box conditions are 120°C, 2 bar and 100% relative humidity. From the data in Table 2, it can be seen that the weight loss rate of Example 1 at 24h, 48h, 72h, and 96h (0.02mg / cm², 0.04mg / cm², 0.08mg / cm², and 0.15mg / cm², respectively) is significantly lower than that of Comparative Example 1 (corresponding to 0.13mg / cm², 0.18mg / cm², 0.31mg / cm², and 0.38mg / cm²). This fully proves that the corrosion-resistant grain boundary diffusion process of the present invention can greatly improve the corrosion resistance of the magnet and effectively resist corrosion in high temperature and high humidity environments.

[0094] Similarly, by comparing Examples 2 to 5 with Example 1, the corrosion weight loss rates of the magnets under different process parameter changes are also different, which once again reflects the regulatory effect of process parameters on corrosion resistance.

[0095] The above mentioned contents only show some preferred examples of the present invention among many possible implementation methods, and are intended to illustrate the innovation and practical application value of the present invention through specific cases. From the detailed embodiments and the carefully designed comparative analysis, we can clearly observe that the present invention successfully achieves a significant improvement in the corrosion resistance of the magnet by introducing a diffusant and combining the grain boundary diffusion process described in the present invention.

[0096] Specifically, this specific ratio of diffusant plays a vital role in the grain boundary diffusion process. It can form a layer of intergranular Li-rich protective material on the surface of the magnet, effectively isolating the direct contact between the external corrosive medium and the inside of the magnet, thereby significantly improving the corrosion resistance of the magnet. At the same time, this innovative diffusion process not only improves the corrosion resistance, but also cleverly maintains the original magnetic properties of the magnet, avoiding the problem of magnetic property degradation commonly seen in traditional treatment methods.

[0097] The present invention not only successfully solves the difficult problem of improving the corrosion resistance of magnets and maintaining their magnetic properties, but also provides new ideas and methods for optimizing the performance of magnet materials, and has broad application prospects and social and economic value.

[0098] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a corrosion-resistant grain boundary diffusion NdFeB magnet, characterized in that: The base magnet is composed of RE in wt.% x Fe (100-x-a-b) B a M b , 33wt%≥x≥29.5wt%, 1.05wt%≥a≥0.92wt%, wherein RE is one or more of Pr, Nd, Dy, Tb, Ho, Ce, and Y in the lanthanide rare earth elements, B is at least one of Dy and Tb, and M is one or more of Co, Zr, Ti, Nb, Cu, Ga, Al, and Zn, and the preparation method comprises the following steps: Step S1, obtaining a sintered NdFeB blank as a base magnet; Step S2, obtaining a diffusion source and preparing a grain boundary diffusion agent, wherein the diffusion source is Zn in weight percent. α Li β Mn 100-α-β Alloy, 60wt.%≥α≥10wt.%; Step S3, machining the sintered NdFeB blank; Step S4, coating the diffusant on the surface of the magnet to obtain a composite magnetic sheet; Step S5, subjecting the composite magnetic sheet to grain boundary diffusion heat treatment, the primary heat treatment temperature is 850-1000°C, the time is 2-8h, after reaching the primary heat treatment temperature, 0.5-1.5h, 50-80kPa high purity argon is given, and then discharged through the vacuum system, and the vacuum degree is maintained for the rest of the primary heat treatment time. -5 The secondary heat treatment temperature is 450-600℃, the time is 2-6h, and the vacuum degree is maintained at 10 -5 After the two-stage heat treatment, argon gas is introduced to make the gas pressure in the furnace reach 80-100kPa, and rapid cooling is performed to obtain corrosion-resistant grain boundary diffusion NdFeB magnets.

2. The preparation method according to claim 1, characterized in that: In step S2, the diffusing agent ratio is 60-80wt.% of diffusion source, 2-5wt.% of binder, and 15-38wt.% of solvent.

3. The preparation method according to claim 2, characterized in that: The binder uses polyvinyl butyral or polyvinyl alcohol.

4. The preparation method according to claim 2, characterized in that: The solvent used is anhydrous ethanol or ether.

5. The preparation method according to claim 2, characterized in that: The diffusion source Zn α Li β Mn 100-α-β In the alloy, 60wt.%≥α≥10wt.%, 80wt.%≥β≥0wt.%, and the mass ratio of the diffusion source: the binder: the solvent is 68±2: 4±0.5: 28±2.

5.

6. The preparation method according to claim 2, characterized in that: In step S3, the blank is machined by wire-cutting with electric sparks, and the axial and radial dimensions are controlled to be no more than 20 mm.

7. The preparation method according to claim 6, characterized in that: In step S3, after the blank is machined, it is sandblasted to clean the surface to remove oil and oxides, and is soaked in a nitric acid solution with a volume ratio of 2.5-5% for 20-30 seconds. After pickling, it is ultrasonically vibrated in alcohol for 2-5 minutes and dried for later use.

8. The preparation method according to claim 1, characterized in that: In step S4, the diffusant is coated by immersing the magnetic sheet, spraying or printing, and step S4 is performed within 1 hour after step S3. The thickness of the diffusant is 0.5-0.6 mm. After the surface of the diffusant is coated, it is dried in an oven at a temperature of 60-80°C for 30-60 minutes.

9. A corrosion-resistant grain boundary diffused NdFeB magnet, characterized in that: Obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for manufacturing sintered Nd-Fe-B magnet on basis of vapor deposition heat treatment for fine powder

    CN103050268A

  • Treating method for improving performance of sintered NdFeB (neodymium iron boron) materials

    CN104681225A

  • Grain boundary diffusion neodymium-iron-boron magnet base material and preparation method of grain boundary diffusion neodymium-iron-boron magnet

    CN119252635A

  • Method of manufacturing magnetic material for bonded magnet and rare earth bonded magnet produced by using this magnetic material

    JP2008069415A

  • Corrosion resistant rare earth magnet and its preparation

    US20030079805A1

Cited By

  • Method for improving corrosion resistance of cerium-rich NdFeB magnet without heavy rare earth

    CN120545085A